Interaction Between the Sodium‐Glucose–Linked Transporter 2 Inhibitor Dapagliflozin and the Loop Diuretic Bumetanide in Normal Human Subjects - Wilcox, Christopher S.; Shen, Wen; Boulton, David W.; Leslie, Bruce R.; Griffen, Steven C. (Journal of the American Heart Association, 2018)
Background Dapagliflozin inhibits the sodium‐glucose–linked transporter 2 in the renal proximal tubule, thereby promoting glycosuria to reduce hyperglycemia in type 2 diabetes mellitus. Because these patients may require loop diuretics, and sodium‐glucose–linked transporter 2 inhibition causes an osmotic diuresis, we evaluated the diuretic interaction between dapagliflozin and bumetanide. Methods and Results Healthy subjects (n=42) receiving a fixed diet with ≈110 mmol·d−1 of Na+ were randomized to bumetanide (1 mg·d−1), dapagliflozin (10 mg·d−1), or both for 7 days, followed by 7 days of both. There were no meaningful pharmacokinetic interactions. Na+ excretion increased modestly with the first dose of dapagliflozin (22±6 mmol·d−1; P<0.005) but by more (P<0.005) with the first dose of bumetanide (74±7 mmol·d−1; P<0.005), which was not significantly different from both diuretics together (80±5 mmol·d−1; P<0.005). However, Na+ excretion with dapagliflozin was 190% greater (P<0.005) when added after 1 week of bumetanide (64±6 mmol·d−1), and Na+ excretion with bumetanide was 36% greater (P<0.005) when added after 1 week of dapagliflozin (101±8 mmol·d−1). Serum urate was increased 4% by bumetanide but reduced 40% by dapagliflozin or 20% by combined therapy (P<0.05). Conclusions First‐dose Na+ excretion with bumetanide and dapagliflozin is not additive, but the weekly administration of one diuretic enhances the initial Na+ excretion with the other, thereby demonstrating mutual adaptive natriuretic synergy. Combined therapy reverses bumetanide‐induced hyperuricemia. This requires further study in diabetic patients with hyperglycemia who have enhanced glycosuria and natriuresis with dapagliflozin. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT00930865.